A virulence activator of a surface attachment protein in Burkholderia pseudomallei acts as a global regulator of other membrane-associated virulence factors - Sun, Zhenxin; Heacock-Kang, Yun; McMillan, Ian A.; Cabanas, Darlene; Zarzycki-Siek, Jan; Hoang, Tung T. (Frontiers in Microbiology, 2023)
Burkholderia pseudomallei (Bp), causing a highly fatal disease called melioidosis, is a facultative intracellular pathogen that attaches and invades a variety of cell types. We previously identified BP1026B_I0091 as a surface attachment protein (Sap1) and an essential virulence factor, contributing to Bp pathogenesis in vitro and in vivo. The expression of sap1 is regulated at different stages of Bp intracellular lifecycle by the unidentified regulator(s). Here, we identified SapR (BP1026B_II1046) as a transcriptional regulator that activates sap1, using a high-throughput transposon mutagenesis screen in combination with Tn-Seq. Consistent with phenotypes of the Δsap1 mutant, the ΔsapR activator mutant exhibited a significant reduction in Bp attachment to the host cell, leading to subsequent decreased intracellular replication. RNA-Seq analysis further revealed that SapR regulates sap1. The regulation of sap1 by SapR was confirmed quantitatively by qRT-PCR, which also validated the RNA-Seq data. SapR globally regulate genes associated with the bacterial membrane in response to diverse environments, and some of the genes regulated by SapR are virulence factors that are required for Bp intracellular infection (e.g., type III and type VI secretion systems). This study has identified the complex SapR regulatory network and its importance as an activator of an essential Sap1 attachment factor.